ISO 9000: Link between Seeking Certification and Perceived Benefit - Yahya, Salleh (Universiti Putra Malaysia Press, 2004)
This paper presents the result of a study on perceived benefits of obtaining ISO 9000 certification. In addition, the link between the intentions of seeking ISO certification with perceived benefit was explored. The results were based on a survey of 405 Malaysian companies with 307 being ISO companies and 98 non-ISO companies. The study revealed that three internal benefits were expected from ISO exercise: (1) Better Documentation (2), Greater Quality Awareness, and (3) Improved Measurement System. For external benefits, these items were identified: (1) Improved Customer Satisfaction, (2) Higher Perceived Quality, and (3) Competitive Edge. Statistical results on the link between the reason for seeking the certificate with perceived benefit have indicated that companies with developmental reasons have higher perceived internal benefits in areas such as: (1) Reductions in Scrap, (2) Improved Departmental Co-operation, (3) Greater Quality Awareness, and (4) Higher Preventive Action, as compared to non-developmental companies. For pair developmental and mixed, significant difference was only evidenced for greater quality awareness. No significant differences were identified for pair mixed and non-developmental. In terms of external benefits, significant differences were not found for any combination of reason seeking certification. This may be due to the fact that external benefits were exogenous factors that could not be considered as reasons for seeking certification.